. Diagnostic Values of Noradrenaline, procalcitonin (PCT), blood lactic acid for Septic Shock: Diagnostic Values of Noradrenaline, procalcitonin (PCT), blood lactic acid - Sun, Haijun (Journal of Medical Biochemistry, 2024)
Backgrounds: This research was conducted to investigate the influencing factors for the prognosis among patients with sepsis/septic shock and the assessment values of the dose of noradrenaline for patient prognosis. Methods :126 patients with sepsis/septic shock were retrospectively selected and enrolled into survival group (stable disease/discharge, n=91 cases) and death group (voluntary discharge and death, n=35 cases). After that, logistic regression analysis was implemented for the analysis of influencing factors for the prognosis and receiver operating characteristic curve (ROC) was utilized to assess the prognostic values of noradrenaline. Logistic regression analysis was performed for the analysis of procalcitonin (PCT) expression, the scores for high acute physiology and chronic health evaluatin II (APACHE II) and high sepsis related organ failure assessment (SOFA), and large dose of noradrenaline 37 h to 48 h after treatment. Results: They were the independent risk factors for death among patients with sepsis/septic shock (P<0.05). Median survival time (MST) was shorter among patients in high-dose group (9.56d) than among patients in low-dose group (20.67d) (P<0.05). Conclusion: High PCT expression, the scores for high APACHE II and high SOFA, and large dose of noradrenaline 37 h to 48 h after treatment affected the prognosis among patients with sepsis/septic shock. In addition, the dose of noradrenaline could reflect the prognosis.